Empatie a emoce v etnografickém výzkumu: Reflexe nad výzkumem percepce smrti - Ponocná, Petra (Lidé města, 2018)
Ethnographic research differs from other types of research by literally being an embodied experience. The essential part of ethnographic research is observation and participation, including listening and asking questions about the lives of people, their experiences, and the meanings they give to their experiences and lives. Establishing relationships in the field can often result in an ethical challenge, related to this relationship and to personal boundaries, as well as to the problem of binding after the ethnographer leaves the terrain. If the subject of research requires a thorough / deep sensitivity, the ethnographer finds themselves on thin ice. The researcher can be emotionally influenced by what they do, by the places they find themselves in, and by the answers they receive. In this article, I submit my own methodological reflection on my research on the perception of death in contemporary Mexico City. I focus on the ways in which emotions and empathy can influence the relationship between the researcher and the informant. An important part of the article is the reflection of the overwhelming emotions experienced, and the actions that must be observed for coping with mental pressure.